2022
DOI: 10.3389/fpubh.2022.840525
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Competitive Risk Model in Elderly Patients With Chromophobe Cell Renal Carcinoma: A Population-Based Study

Abstract: BackgroundRenal cell carcinoma (RCC) is the most common renal malignancy in adults, and chromophobe renal cell carcinoma (chRCC) is the third most common subtype of RCC. We aimed to construct a competitive risk model to predict cancer-specific survival (CSS) in elderly patients with chRCC.MethodsThe clinicopathological information of the patients was downloaded from the SEER database, and the patients were randomly divided into the training and validation cohorts. Patients' risk factors for cancer-specific dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The cumulative risk model was used to estimate the cumulative incidence of cancer-specific death. Based on Fine and Gray's proportional sub-distribution hazard model, the influencing factors of cancer-specific death were analyzed [ 19 , 20 ]. Proportional sub-distribution hazard model is a direct extension of Cox model in competitive risk situations.…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative risk model was used to estimate the cumulative incidence of cancer-specific death. Based on Fine and Gray's proportional sub-distribution hazard model, the influencing factors of cancer-specific death were analyzed [ 19 , 20 ]. Proportional sub-distribution hazard model is a direct extension of Cox model in competitive risk situations.…”
Section: Methodsmentioning
confidence: 99%
“…The accurate prediction of cancer control outcomes in RCC patients is important for counselling, the planning of follow-up and the selection of appropriate adjuvant trial designs. Several prognostic models incorporating clinical and pathological RCC variables have been validated to predict recurrence and mortality after nephrectomy in chRCC [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Of these, two models are recommended by European guidelines to predict cancer control outcomes after nephrectomy in non-metastatic chRCC [ 15 ]: Leibovich 2018 [ 2 , 16 ] and GRade, Age, Nodes and Tumor (GRANT) [ 3 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there have been few studies exploring the influencing factors of death for localized PCa patients. In recent years, Cox model and competitive risk models have been gradually applied in the prediction of mortality for different cancers ( 11 , 12 ). Furthermore, it was reported that compared with the Cox model, the Fine-Gray proportional model for competing risks provides a better estimation for the risk of the main outcome of benefit when one or more competing risks exist ( 13 ).…”
Section: Introductionmentioning
confidence: 99%